PTHrP promotes development of mouse preimplantation embryos through the AKT/cyclin D1 pathway and nuclear translocation of HDAC4. Issue 10 (16th March 2021) - Li, Yuan‐Yuan; Guo, Lei; Li, Hui; Lei, Wen‐Long; Fan, Li‐Hua; Ouyang, Ying‐Chun; Hou, Yi; Wang, Zhen‐Bo; Sun, Qing‐Yuan; Lu, Sheng‐Sheng; Han, Zhiming
Abstract: Parathyroid hormone‐related protein (PTHrP), the main cause of humoral hypercalcemia in malignancies, promotes cell proliferation and delays terminal cell maturation during embryonic development. Our previous study reported that PTHrP plays important roles in blastocyst formation, pluripotency gene expression, and histone acetylation during mouse preimplantation embryonic development. In this study, we further investigated the mechanism of preimplantation embryonic development regulated by PTHrP. Our results showed that Pthrp depletion decreased both the developmental rate of embryos at the cleavage stage and the cell number of morula‐stage embryos. Pthrp ‐depleted embryos had significantly decreased levels of cyclin D1, phospho (p)‐AKT (Thr308) and E2F1. However, Pthrp depletion did not cause significant changes in CDK4, β‐catenin or RUNX2 expression. In addition, our results indicated that Pthrp depletion promoted HDAC4 translocation from the cytoplasm to the nucleus in cleavage‐stage embryos by stimulating the activity of protein phosphatase 2A (PP2A), which resulted in dephosphorylation of HDAC4. Taken together, these results suggest that PTHrP regulates cleavage division progression and blastocyst formation through the AKT/cyclin D1 pathway and that PTHrP modulates histone acetylation patterns through nuclear translocation of HDAC4 via PP2A‐dependent HDAC4 dephosphorylation during preimplantation embryonic development in mice. Abstract : The authors demonstrate that parathyroid hormone‐related protein (PTHrP) regulates mouse preimplantation embryonic development through the AKT/cyclin D1 pathway, and that PTHrP modulates histone acetylation pattern through nuclear translocation of HDAC4 via PP2A‐dependent HDAC4 dephosphorylation during mouse preimplantation embryonic development. This study suggests that PTHrP regulates mouse preimplantation embryonic development through the cyclin D1/AKT pathway and nuclear translocation of HDAC4.